Chromium Oxynitride Electrocatalysts for Electrochemical Synthesis of Ammonia Under Ambient Conditions. Issue 6 (21st October 2018) - Yao, Yao; Feng, Qi; Zhu, Shangqian; Li, Jiadong; Yao, Yuze; Wang, Yajun; Wang, Qi; Gu, Meng; Wang, Haijiang; Li, Hui; Yuan, Xiao‐Zi; Shao, Minhua
Abstract: The electrochemical synthesis of ammonia via nitrogen reduction reaction (NRR) has received much attention as a more environmentally friendly and less energy consuming technology than the conventional Haber–Bosch process. The catalytic activities of all NRR electrocatalysts reported so far, however, are very low under ambient conditions. In this study, partially oxidized chromium nitride (chromium oxynitride) nanoparticles are synthesized and their NRR activities are evaluated in a proton exchange membrane electrolyzer under ambient conditions. The highest ammonia formation rate of 8.9 × 10 −11 mol s −1 cm −2 and 15.56 µg h −1 mg −1 cat are achieved at a cell voltage of 2.0 V. The highest Faradaic efficiency of 6.7% is achieved at a cell voltage of 1.8 V. The findings demonstrate that metal nitride–based materials can be promising electrocatalysts toward NRR and could guide rational design of more advanced catalysts for various reactions. Abstract : Partially oxidized chromium nitride (chromium oxynitride) nanoparticles are synthesized and their nitrogen reduction reaction activities are evaluated in a proton exchange membrane electrolyzer under ambient conditions. The highest ammonia formation rate of 8.9 × 10 −11 mol s −1 cm −2 and Faradaic efficiency of 6.7% are achieved at 2.0 and 1.8 V, respectively.